Implementasi Pemasaran Syariah Melalui Pembuatan Lilin Aromaterapi dari Minyak Jelantah di RT 19 Kelurahan Bumi Ayu - Putri, Alfiah Thalia Nabila; Utami, Lili; Atikah, Nabilah Nur; Fryanti, Yunida Een (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to implement the concept of sharia marketing in community empowerment activities through the manufacture of aromatherapy candles from used cooking oil in RT 19, Bumi Ayu Village. This activity was motivated by the desire to utilize household waste, especially used cooking oil, into products with economic value and are environmentally friendly. The approach used is a participatory method by directly involving residents in training, production, and marketing strategies. Sharia marketing is implemented by emphasizing the principles of honesty, transparency, and blessings in every stage of the process. The results of the activity showed an increase in residents' understanding of the values of the circular economy and the basic principles of sharia marketing. Aromatherapy candle products from used cooking oil also received a positive response from local consumers, showing the potential for sustainable businesses based on Islamic values. This study recommends the development of similar activities as a model for community empowerment based on the creative economy and Islamic ethics.